Identification of Alpha-Gal glycolipids in saliva of Lone-Star Tick (Amblyomma americanum) - Surendra Raj Sharma; Sabir Hussain; Shailesh K. Choudhary; Scott P. Commins; Shahid Karim (Ticks and Tick-Borne Diseases)
Alpha-Gal Syndrome (AGS) is a delayed allergic reaction triggered by IgE antibodies targeting galactose-α-1,3-galactose (α-gal), prevalent in red meat. Its global significance has increased, with over 450,000 estimated cases in the United States alone. AGS is linked to tick bites, causing sensitization and elevated α-gal specific IgE levels. However, the precise mechanisms and tick intrinsic factors contributing to AGS development post-tick bites remain unclear. This study aims to characterize the alpha-gal conjugated lipid antigens in Amblyomma americanum (Am. americanum) salivary glands and saliva. Nanospray ionization mass spectrometry (NSI-MS) analysis revealed the identification of α-gal bound lipid antigens in Am. americanum saliva. Additionally, the activation of basophils by extracted alpha-gal bound lipids and proteins provides evidence of their antigenic capabilities.